Creativity in motion: an analysis of the creative processes at Mauricio de Sousa Produções - Salles, Cecilia Almeida; Francini, Guilherme (Farol, 2024)
In his more than 60-year career as a comic artist, Mauricio de Sousa has built a legacy deeply rooted in Brazilian culture. Through his studio, Mauricio de Sousa Produções (MSP), he has faced significant technological and social changes. However, his characters remain as popular. This article, through a visit to the studio, research and interviews, seeks to understand the creative processes that enable MSP's dynamism and adaptability in the face of the challenges of new times.
Keywords: process critique, creative process; comics; Mauricio de Sousa; Brazilian children's literature